(untitled) (Historia, 2021)
English This article attempts to provide an insight into the frustrations experienced by African mine-workers at the Messina copper mines as a result of poor wages and service conditions. This led to a sustained deterioration in the social and economic position of the workers. Through a number of labour laws, the South African government had protected the mining industry from labour demands which were seen as threatening not only to the economic stability of the mining industry, but also to the mining tax revenue of the State. The article also attempts to prove that the outbreak of the 1943 strike at the Messina copper mines was a visible manifestation of a permanent alienation and conflict, a sign that the contradictions in the economic and social systems at these mines were growing and that the struggle between mine management and the workers was assuming a sharper and an irrepressible form. During the strike period, the government did not hesitate to use police and military force to compel labour to succumb to capital-State requirements. Afrikaans Op Soek na Beter Lone: Mynbou Kapitalisme en Staatsmag word uitgedaag, 1943 Hierdie artikel poog om insig te bied in die frustrasies van swart mynwerkers in die Messina kopermyne as gevolg van swak betaling en haglike werksomstandighede. Dit het gelei tot ŉ volgehoue verswakking in die sosiale en ekonomiese posisie van die werkers. Die regering het ŉ aantal arbeidswette gebruik om die mynbou-industrie te beskerm teen arbeiders se eise. Laasgenoemde is nie net gesien as ŉ bedreiging vir die ekonomiese stabiliteit van die mynbou-industrie nie, maar ook vir die belastingopbrengs wat die regering uit mynbou geput het. Die artikel bewys verder dat die uitbreek van die 1943-staking ŉ sigbare manifestasie van permanente vervreemding en konflik was, asook ŉ teken daarvan dat kontradiksies in die ekonomiese en sosiale sisteme by die Messina kopermyne aan die toeneem was en dat die stryd tussen mynbestuur en werkers besig was om ŉ skerper en ononderdrukbare vorm aan te neem. Gedurende die staking het die regering nie gehuiwer om die polisie en militêre mag te gebruik om werkers te dwing om toe te gee aan die vereistes van kapitalisme en die Staat nie.